Down-regulation of interleukin-1 receptor and toll-like receptor pathways in neutrophils following prolonged, intense exercise - Neubauer, O.; Sabapathy, S.; Lazarus, R.; Ashton, K.; Desbrow, B.; Jowett, J.; Cameron-Smith, D.; Haseler, L.; Wagner, K. H.; Bulmer, A. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Introduction: Prolonged, strenuous exercise induces a systemic inflammatory response that is followed by counter-regulatory and antiinflammatory responses during the recovery period (Neubauer et al., 2008). Neutrophils play an essential role in these responses, and they are critical for tissue repair, remodelling, growth (Walsh et al., 2011), and the resolution of inflammation (Theilgaard-Mönch et al., 2006). Evidence is emerging that the underlying mechanisms in neutrophils are regulated by highly coordinated transcriptional programs (Radom-Aizik et al., 2008). Aim This study aimed to investigate the gene expression changes in circulating neutrophils following an experimental exercise trial (EXTRI) consisting of two hours (h) of intense, continuous cycling and running. We hypothesised that gene expression responses in neutrophils during recovery reflect the regulation of pathways involved in the systemic inflammatory response, and in subsequent counter-regulatory mechanisms. Methods: Eight healthy, endurance-trained, male subjects (age: 25.0 ± 4.1 years; VO2 peak: 56.3 ± 6.7 mL/kg/min) participated. Skeletal muscle and blood samples were taken one week before the EXTRI (baseline), and 3 h, 48 h, and 96 h post-EXTRI under standardized conditions. Microarray analysis was performed using the Illumina iScan platform. Differential expression in a paired design was tested using lumi and limma from Bioconductor. Gene set enrichment analysis (GSEA) was used to identify enriched molecular signatures chosen from the Molecular Signatures Database. Differentially expression of selected genes was confirmed via RT-qPCR. Results: Circulatory neutrophil counts increased 3 h post-EXTRI (P<0.001) and returned to baseline 48 h post-EXTRI. Genes associated with neutrophil activation (eg., CAMP), viability (eg., SOD2, MCL1), and tissue damage (eg., S100A12) were up-regulated 3 h post-EXTRI (P<0.05). GSEA indicated an up-regulation of the interleukin (IL)-1 receptor (IL1R) and toll-like receptor (TLR) pathways 3 h post-EXTRI (FWER p-value < 0.05). Up-regulated genes that are associated with these pathways included IL1RN (encoding the antiinflammatory cytokine IL-1 receptor antagonist), IRAK3 (a negative regulator of IL1R-/TLR-signalling), IL1R1, TLR6, and FADD (a regulator of TLR-mediated apoptosis, and a negative regulator of innate immune signalling). Discussion: The transcriptional regulation of IL1R- and TLR-pathways indicates the acute activation of innate immune cellular activity in response to exercise. The up-regulation of IL1RN, IRAK3, and FADD appear to contribute to an early counter-regulation of these pathways. These data suggest a novel mechanism, by which neutrophils negatively regulate the innate immune response to exercise to avoid overshooting inflammation.